PENGEMBANGAN MEDIA PEMBELAJARAN MINIATUR MATERI ENERGI ALTERNATIF UNTUK SISWA KELAS IV SEKOLAH DASAR - Novalia Nidya Permata; Wahid Ibnu Zaman; Susi Damayanti (STKIP PGRI Situbondo, 2022)
The problem in this study is the lack of use of media in the learning process. This indirectly affects student learning outcomes. This type of research is research and development (r&d), researchers develop miniature learning media (Windmills and Solar Panels) on alternative energy sources for grade IV Elementary School. The purpose of the study was to determine student learning outcomes using miniature media. This study took samples from 28 students of SDN MRICAN 1 Kediri City. The development model used in this research is ADDIE. The ADDIE model has five stages, namely (1) Analysis (2) Design (3) Development (4) Implementation (5) Evaluation. The data collection technique used is in the form of a questionnaire through data analysis techniques of validity, practicality, and effectiveness. The results of the research on the development of miniature learning media obtained include: (1) the development of miniature learning media for class IV alternative energy sources at SD Negeri Mrican 1 in accordance with the ADDIE development procedure. (2) the miniature media is declared suitable for use seen from: (a) the results of media validation get a percentage value of 90% and material validation obtains a percentage value of 89%, (b) the results of the teacher's practicality questionnaire get a value of 90%, (c) the results of the student response questionnaire in the trials that have been carried out, the percentage value is 91%. Based on the statement above, it can be concluded that miniature media has a significant influence on student learning outcomes on alternative energy sources.